2015
DOI: 10.3233/jnd-150100
|View full text |Cite
|
Sign up to set email alerts
|

Non-Ambulant Duchenne Patients Theoretically Treatable by Exon 53 Skipping have Severe Phenotype

Abstract: Background: Exon skipping therapy is an emerging approach in Duchenne Muscular Dystrophy (DMD). Antisense oligonucleotides that induce skipping of exon 51, 44, 45, or 53 are currently being evaluated in clinical trials. These trials were designed on the basis of data available in general DMD population. Objectives: Our objective was to compare the clinical and functional statuses of non-ambulant DMD patients theoretically treatable by exon 53 skipping and of DMD patients with other mutations. Methods: We first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 30 publications
(24 reference statements)
2
50
1
Order By: Relevance
“…Retrospective data on loss of ambulation and other features of disease progression [5, 6] in patients with deletions amenable to skip exon 44, 45, 51 and 53 have recently become available, but only few have reported prospectively collected longitudinal data in these subgroups of patients[79]. These papers suggest that the changes in the individual subgroups do not appear to be significantly different from the mean changes observed in the whole cohort of DMD patients over a year [7], but the difference becomes more obvious on a longer follow up (24 months), especially when individual subgroups were compared to each other [8].…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective data on loss of ambulation and other features of disease progression [5, 6] in patients with deletions amenable to skip exon 44, 45, 51 and 53 have recently become available, but only few have reported prospectively collected longitudinal data in these subgroups of patients[79]. These papers suggest that the changes in the individual subgroups do not appear to be significantly different from the mean changes observed in the whole cohort of DMD patients over a year [7], but the difference becomes more obvious on a longer follow up (24 months), especially when individual subgroups were compared to each other [8].…”
Section: Introductionmentioning
confidence: 99%
“…One limitation is potential generalization of such results to the overall DMD population. Although patients potentially treatable by exon 53 skipping tend to have more severe symptoms than the overall DMD population, 26 evolution over a 1-year period is similar to that of the general DMD population (data not shown). Several possible reasons could underlie the more severe phenotype of these patients: they may be smaller in stature compared to other patients with DMD, may have a smaller number of revertant fibers, and may have a weaker response to steroids.…”
Section: Discussionmentioning
confidence: 74%
“…In the available data from the Duchenne Registry, we were able to retain a substantial number (N = 765) of males with an exonic duplication, nonsense mutation, or deletion mutation correctable by skipping exon 8, 44, 45, 50, 51, 52, 53, or 55 alongside their steroid usage and age at LOA. The availability of these multiple data types and the ability of participants to update data make the Duchenne Registry a robust data set for exploratory studies and natural history comparison because it is larger than all reported studies investigating DMD age at LOA combined (Bello et al, 2016;Pane et al, 2014;Servais et al, 2015;van den Bergen, et al, 2014). (Bello et al, 2016;van den Bergen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%